Ascorbyl palmitate interaction with phospholipid monolayers: electrostatic and rheological preponderancy - Mottola, Milagro (2013)
Ascorbyl palmitate (ASC16) is an anionic amphiphilicmolecule of pharmacological interest due to its antioxidant properties. We found that ASC16 strongly interacted with model membranes. ASC16 penetrated phospholipid monolayers, with a cutoff near the theoretical surface pressure limit. The presence of a lipid filmat the interface favored ASC16 insertion compared with a bare air/water surface. The adsorption and penetration time curves showed a biphasic behavior: the first rapid peak evidenced a fast adsorption of charged ASC16 molecules to the interface that promoted a lowering of surface pH, thus partially neutralizing and compacting the film. The second rise represented an approach to the equilibrium between the ASC16 molecules in the subphase and the surface monolayer, whose kinetics depended on the ionization state of the film. Based on the Langmuir DMPC + ASC16 monolayer data, we estimated an ASC16 partition coefficient to DMPC monolayers of 1.5 × 105 30 Q2 and a ΔGp = −6.7 kcal·mol 31 −1. The rheological properties of the host membrane were determinant for ASC16 penetration kinetics: a fluid membrane, as provided by Chol, disrupted the liquid-condensed ASC16-enriched domains and favored ASC16 penetration. Subphase pH conditions affected ASC16 aggregation in bulk: the smaller structures at acidic pHs showed a faster equilibrium with the surface film than large lamellar ones. Our results revealed that the ASC16 interaction withmodelmembranes has a highly complex regulation. The polymorphism in the ASC16 bulk aggregation added complexity to the equilibrium between the surface and subphase form of ASC16, whose understanding may shed light on the pharmacological function of this drug.